2020
DOI: 10.1049/iet-map.2019.0806
|View full text |Cite
|
Sign up to set email alerts
|

Broadband omnidirectional patch antenna with horizontal gain enhanced by near‐zero‐index metamaterial cover

Abstract: Enhancing the horizontal gain of the omnidirectional patch antenna is always a problem with great difficulty. Inspired by near‐zero‐index metamaterial (NZIM) cover that can improve the vertical gain of a directional patch antenna, the authors designed two kinds of NZIMs that are placed above the broadband omnidirectional antenna to enhance the horizontal gain. Simulated and measured results indicate that both covers can increase the values of horizontal gain >50% (1 dBi) at various frequencies in all direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The comparison of Antenna 2a and 2b with other works in publications is illustrated in Table 3. We can conclude from the [15] and the size of our antenna is larger, but our antenna has great advantage in profile compared with these antennas. When compared with other antennas, the horizontal gain of Antenna 2b is maximum.…”
Section: Comparison and Discussion Of The Measured Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The comparison of Antenna 2a and 2b with other works in publications is illustrated in Table 3. We can conclude from the [15] and the size of our antenna is larger, but our antenna has great advantage in profile compared with these antennas. When compared with other antennas, the horizontal gain of Antenna 2b is maximum.…”
Section: Comparison and Discussion Of The Measured Resultsmentioning
confidence: 80%
“…NZIM metamaterials are rarely used to increase the horizontal gain of the omnidirectional antenna. We have successfully improved the gain of omnidirectional antenna by applying epsilon-negative metamaterial (ENG) or NZIM covers in the previous works [14,15]. However, the problem of profile is not well solved.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that bandwidth is decreased for the antenna with MTM with a downward shift of upper cutoff frequency. It can be explained by using the impedance matching of the equivalent circuit of the antenna as impedance, Z and frequency, f of resonance can be expressed 51 as, and respectively, in which L corresponds to total inductance and C is the capacitance. Introducing the MTM with antenna causes a modification of the total capacitance, thus resonance frequency shifts.…”
Section: Gain Enhancement Of Antenna Using Mtm Superstrate With Antennamentioning
confidence: 99%
“…33 b. Thus, MTM cover helps to increase horizontal electromagnetic wave, which in turn enhance horizontal gain due to the change of direction of the main beam 53 . 3D far-field radiation pattern is presented in Fig.…”
Section: Application: Gain Enhancement Of Tapered Log Periodic Dipole(tlpd) Antenna Using An Array Of Proposed Mtmmentioning
confidence: 99%